An Efficient And High Performance Architecture Design And Implementation Approach Of Cryptographic Algorithm Computation For Authentication In Modern Wireless Communication Applications - et. al., Lega.Karunankitha , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
According to the general reflections in the former section, the following goals are for this proposed work. The aim of the proposed work is implementation of the hardware architecture for L.M. Montgomery Modular Multiplication Algorithmic and proposes a mountable systolic architecture which is operative for large bit-lengths and it is appropriate for equally regularly used categories of open Key Cryptography (PKC) i.e. ECC and RSA Crypt-systems. The open key algorithms such as RSA ,Diffed-Hellman key exchange and Elliptical curve cryptography make use of high end computational operations like exponentiation which can be computed by using fast implementation of Montgomery modular exponentiation method. Here developing the Montgomery modular multiplication technique is aimed. The main aim of this procedure is to reduce the requirement of area and time because the less area x time factor is very useful for realizing in to hardware for real time applications.